Penggunaan Metode Jalur Kritis pada Manajemen Proyek (Studi Kasus: PT. Trend Communications International) - Nurvelly Rosanti; Erwin Setiawan; Asti Ayuningtyas (Prosiding Seminar Nasional Teknoka, 2016)
Project Management has been an important part of software development projects, therefore the use of technology to endorse effectiveness and efficiency of Project Management is a crucial aspect. PT. Trend Communications Internation (TRENDcom) is a company providing Project Management Office (PMO) service. Their main service is to provide expertise in managing Information Technology projects. One of the big issues they are facing is managing timeline. Late of delivery is caused by people, process and technology reasons. Technology-wise, the absence of application to let project manager and his PMO team the important activities that will cause delay on overall progress as well as the lack of reminder for their due project activities. Using Critical Path Method, an application is developed to address the issues. The application managed to give information of activities in a schedule which has big impact on overall delivery timeline and to provide reminder of due activities.